China and Europe’s Partnership for a More Sustainable World Challenges and Opportunities - Spigarelli, Francesca; Curran, Louise; Arteconi, Alessia (Emerald Group Publishing Limited, 2016)
This book gathers the main scientific outputs of POREEN, a four-year project on partnering opportunities between Europe and China in the renewable energy and environmental industries. It investigates the main challenges and opportunities related to Sino-European dialogue and cooperation in the green sector with a focus on sustainable growth